Seleksi dan Penentuan Third Party Logistik Transportasi Produk Pelumas Menggunakan Metode TOPSIS dan PROMETHE - Sawarni Hasibuan; Choesnul Jaqin (Universitas Mercu Buana, 2022)
Selection of Third Party Logistics (3PL) services is an important focus of attention for companies in selecting suppliers in their supply chain. The wide marketing area of PT PETRONAS's lubricant products demands 3PL performance to increase the company's service level. The purpose of this study is to analyze the decision-making process in the context of selecting 3PL transportation suppliers using the TOPSIS and PROMETHE multi-criteria methods. The type of data used consists of primary data and secondary data through library research, interviews, and field surveys. The process of selecting a transportation 3PL is carried out in two stages, namely selection of criteria and the commercial aspect of the bidding price per region is evaluated as the basis for selecting the best supplier. The selected suppliers are PT Wira Logitama Saksama, PT Glory sogotrans Mandiri, PT Iron Bird Logistik, PT Sumisho Global Logistik, and PT Dunia Express Transindo. Based on the results of the analysis using the PROMETHEE method, five criteria with the highest weight were produced, namely Price, Time Delivery, Health Safety Management, Infrastructure and Office Equipment. The results of the ranking using the TOPSIS method for shipping to each destination are that PT Wira Logitama Semesta is the best supplier for five shipping destinations, namely Jabodetabek, Bandung, Surabaya, Lampung and Medan and PT Iron Bird Logistik is the best supplier for shipping to Cilegon and Semarang.